Sarcopenia among hospitalized patients: 1 cross-sectional study - Sousa, A.S. (2015)
Background & aims: Data on the prevalence of sarcopenia among hospitalized older patients are scarceand there is no available information on the burden of sarcopenia among younger patients. The presentstudy aims to increase the knowledge about the frequency of sarcopenia among hospitalized patientsand to evaluate the influence of different diagnostic criteria in these estimates.Methods: A cross-sectional study was conducted in hospitalized adult patients. Sarcopenia was defined,according to the European Working Group on Sarcopenia in Older People (EWGSOP), as the presence ofboth low muscle mass, assessed by Bioelectrical Impedance Analysis (BIA), adjusted for height, and lowmuscle function (hand grip strength). Two other criteria were applied, also using hand grip strength forevaluating muscle function, one that also assessed muscle mass by BIA, but adjusted for weight, andanother which estimated muscle mass based on mid-arm muscle circumference. Nutritional status wasevaluated by Patient-Generated Subjective Global Assessment. The degree of agreement between thedifferent diagnostic criteria was assessed using kappa. Multivariable logistic regression models wereused in order to identify factors associated with sarcopenia.Results: 608 hospitalized adult patients aged 18 years composed the study sample. According toEWGSOP's criteria, 25.3% patients were sarcopenic. However, depending on age and on the appliedcriteria, frequency of sarcopenia varied from 5% to 41.1% for men and from 4.9% to 38.3% for women.There was 95.7% (k Œ 0.89) agreement between criteria that estimated muscle mass by BIA. According toEWGSOP criteria approximately 20% of the non-undernourished patients were sarcopenic. Furthermore,29.5% of overweight and 18.7% of obese patients were sarcopenic. Factors associated with sarcopeniawere male gender, age 65 years, moderate or severe dependence, being undernourished and admittedto a medical ward.Conclusions: Sarcopenia is frequent among hospitalized patients and varies widely depending on theapplied diagnostic criteria. Sarcopenia was identified in a considerable proportion of patients aged under65 years and in non-undernourished, namely among overweight and obese.